Sedimentary processes of the Bagnold Dunes: Implications for the eolian rock record of Mars. Issue 12 (7th December 2017) - Ewing, R. C.; Lapotre, M. G. A.; Lewis, K. W.; Day, M.; Stein, N.; Rubin, D. M.; Sullivan, R.; Banham, S.; Lamb, M. P.; Bridges, N. T.; Gupta, S.; Fischer, W. W.
Abstract: The Mars Science Laboratory rover Curiosity visited two active wind‐blown sand dunes within Gale crater, Mars, which provided the first ground‐based opportunity to compare Martian and terrestrial eolian dune sedimentary processes and study a modern analog for the Martian eolian rock record. Orbital and rover images of these dunes reveal terrestrial‐like and uniquely Martian processes. The presence of grainfall, grainflow, and impact ripples resembled terrestrial dunes. Impact ripples were present on all dune slopes and had a size and shape similar to their terrestrial counterpart. Grainfall and grainflow occurred on dune and large‐ripple lee slopes. Lee slopes were ~29° where grainflows were present and ~33° where grainfall was present. These slopes are interpreted as the dynamic and static angles of repose, respectively. Grain size measured on an undisturbed impact ripple ranges between 50 μm and 350 μm with an intermediate axis mean size of 113 μm (median: 103 μm). Dissimilar to dune eolian processes on Earth, large, meter‐scale ripples were present on all dune slopes. Large ripples had nearly symmetric to strongly asymmetric topographic profiles and heights ranging between 12 cm and 28 cm. The composite observations of the modern sedimentary processes highlight that the Martian eolian rock record is likely different from its terrestrial counterpart because of the large ripples, which are expected to engender a unique scale of cross stratification. More broadly, however, in the Bagnold Dune Field as on Earth, dune‐field pattern dynamics and basin‐scale boundary conditions will dictate the style and distribution of sedimentary processes. Key Points: Impact ripples, grainfall, and grainflows occur on Martian dunes and are similar to terrestrial counterparts Unique, meter‐scale large ripples are found on Martian dunes and would distinguish the Martian and terrestrial eolian rock records The angle of repose on Martian dunes and large ripples is found to be around 29°, which is similar to that found on Earth Plain Language Summary: The Mars Science Laboratory rover Curiosity visited two active wind‐blown sand dunes within Gale crater, Mars, which provided the first opportunity to make a ground‐based observations of sand dunes on Mars. These observations are compared to dunes on Earth and are used as a modern analog for ancient sedimentary rocks on Mars. Dune attributes, such as wind impact ripples and sand flow avalanches, are found to be similar to terrestrial dunes. The avalanches formed between 29 and 40 degrees, which is similar to Earth and supports the idea gravity plays little role in how steeply sand can pile up. The most distinct departure from terrestrial dunes was the presence of meter‐scale ripples superimposed on the dunes. This scale of ripple does not exist on terrestrial dunes and is thought to form because of the low‐atmospheric density on Mars. This scale of ripple would likely manifest as decimeter‐scale wind‐blown cross‐stratification in the Martian rock record, which is an unusual scale for the terrestrial counterpart.